1997
DOI: 10.1159/000227669
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Administered over 3 h Followed by Cisplatin in Patients with Advanced Head and Neck Squamous Cell Carcinoma: A Clinical Phase I Study

Abstract: We have performed a clinical phase I trial of a combination treatment with paclitaxel given as 3-hour infusion and cisplatin to determine the maximum tolerated dose and the dose-limiting toxicity in patients with recurrent or metastatic squamous cell carcinoma of the head and neck. Treatment was repeated every 21 days. Doses administered ranged from 135 mg/m2 paclitax-el/75 mg/m2 cisplatin to 250 mg/m2 paclitaxel/l00 mg/m2 cisplatin. Twenty-four patients have been en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
3
16
1
2
Order By: Relevance
“…Abnormal TE has also been reported in ALS, 8,13 a toxic neuropathy, 20 multifocal motor neuropathy, 14 and in monomelic amyotrophy with spinal hemiatrophy. 17 Although TE is able to reveal otherwise undetectable abnormalities in nerve membranes, its clinical utility has been limited partly by the uncertainties regarding its interpretation.…”
Section: Conventional Electrophysiological Tests Of Nervementioning
confidence: 82%
“…Abnormal TE has also been reported in ALS, 8,13 a toxic neuropathy, 20 multifocal motor neuropathy, 14 and in monomelic amyotrophy with spinal hemiatrophy. 17 Although TE is able to reveal otherwise undetectable abnormalities in nerve membranes, its clinical utility has been limited partly by the uncertainties regarding its interpretation.…”
Section: Conventional Electrophysiological Tests Of Nervementioning
confidence: 82%
“…Consequently, further studies were performed to analyze the activity of paclitaxel-containing regimens. Phase I trials reported by Hanauske et al [9]and Schilling et al [10]showed the feasibility of the administration of paclitaxel and cisplatin at recommended doses of 200 and 100 mg/m 2 every 21 days, respectively. The association of paclitaxel 200 mg/m 2 and cisplatin 100 mg/m 2 obtained a 44% objective response rate, but produced a median overall survival of 7 months [11].…”
Section: Discussionmentioning
confidence: 99%
“…These disturbances in membrane excitability were detected by threshold electrotonus after only one or two doses of chemotherapy, before any clinical or neurological signs of neuropathy. 70 Taxol also depolarized human sural nerves in vitro. 64 …”
Section: Threshold Electrotonus In a Toxicmentioning
confidence: 96%
“…26 Threshold electrotonus has been used to investigate this neuropathy in 15 patients. 36,70 There was a marked symmetrical ''fanning in'' or flattening of the threshold electrotonus responses, indicating that the axons were depolarized or the conductance of the internodal axon membrane was increased. As already mentioned, the axons also became more sensitive to ischemia.…”
Section: Threshold Electrotonus In a Toxicmentioning
confidence: 99%